STUDI DAYA AKTIVASI ARANG SEKAM PADI PADA PROSES ADSORPSI LOGAM Cd - ., Widayanti; Isa, Ishak; Aman, La Ode (Jurnal Sainstek, 2012)
This research aims to find out the ability of activated charcoal rice hurks in the adsorbed metal cadmium in the solvent. The method which is used in this researes are carbonation and activation. The carbonation is doing by close system, the activation is doing by chemical. Activated charcoal produced is tested the absorption of cadmium metal in the solvent. The results showed that activated charcoal which is produced is able to absorb cadmium metal in the solvent that is equal to 19,03 %. The result of proximated analysis of activated charcoal are the water content, volatile matter content, ash content and carbon content are eachboon 13,09%, 15,82%, 53,83% and 30,35%.